A 'light for all humanity': the treaty on the prohibition of nuclear weapons and the progress of humanitarian disarmament. Issue 2 (4th May 2018) - Docherty, Bonnie
ABSTRACT: Reframing nuclear weapons as a humanitarian issue revolutionised the diplomatic debate surrounding them, and in 2017, 122 countries adopted the Treaty on the Prohibition of Nuclear Weapons (TPNW). The humanitarian approach to disarmament provided inspiration for this historic achievement. While traditional disarmament aims primarily to protect state security, humanitarian disarmament strives to end human suffering. This article examines the TPNW as the latest step in humanitarian disarmament. Through a close analysis of process and text, it finds that humanitarian disarmament served as a catalyst to and model for the TPNW's negotiations and shaped its purpose and provisions. The article also shows how the humanitarian underpinnings of the TPNW allowed it to transform nuclear disarmament and how the new treaty strengthened humanitarian disarmament in return.